MODEL STUDY AND APPLICATION ON SURFACE PRESSURE MEASUREMENT OF STRUCTURE WATER ENTRY - ZHANG YueQing; XU Fei; LI JianChen; LI JianFen (Jixie qiangdu)
There will be different loads along the structure surface when it impacts on the water,which has an important effect on the safety of the capsule structure and the people inside. So the research of water impact has a practical significance in the field of aerospace and military. Base on wedge and arc body model,the test of free fall on the water has been investigated on different situations. Firstly the parameter of PVDF is calibrated in the static and dynamic state,using which the distribution of surface pressure is obtained. Then different situations of the experiment are simulated by LS-DYNA and the test pressures are proved further. The pressures are analyzed by different factors. Finally base on the similarity criteria,the impact response of real aircraft structure are obtained by the test data,which has a valuable reference for the design of structure.